Efficacy and safety of traditional Chinese medicine for cancer-related fatigue: a systematic literature review of randomized controlled trials - Jingya Yang; Yuxiao Li; Chi Ian Chau; Junnan Shi; Xianwen Chen; Hao Hu; Carolina Oi Lam Ung (BMC, 2023)
Abstract Background Cancer-related fatigue (CRF) is an extremely common and long-term condition that affects the physical and mental health of oncology patients. While the treatment for CRF with western medicine and non-pharmacological therapy remains uncertain and challenging, traditional Chinese medicine (TCM) has become a trending option for the patients. Based on the findings from randomized controlled trials (RCTs), this study aims to identify and evaluate the evidence about the efficacy and safety of TCM for CRF. Methods A systematic literature search was conducted according to the PRISMA literature research guidelines. Seven electronic databases including PubMed, the Cochrane Library, Embase, Web of Science, Scopus, China National Knowledge Infrastructure (CNKI) and Wanfang database were searched to identify RCTs which investigated TCM in the treatment of CRF published since inception to December 2022. RCTs comparing TCM with no treatment, placebo, or pharmacological interventions were considered eligible for this review. The Consolidated Standards of Reporting Trials Statement extensions for Chinese herbal medicine Formulas (CONSORT-CHM) and the Cochrane Collaboration's Risk of Bias tool were used in this review to evaluate the quality and the risk of bias of all included trials. Results A total of 82 RCTs were included in this review, regardless of whether they were published in English or Chinese. After data extraction and results evaluation, 78 trials demonstrated overall efficacy in using TCM for CRF patients compared with the control group, in which 33 trials showed that the efficacy rate was statistically significant (p < 0.05 or p < 0.01). TCM was also shown to be beneficial in improving the scores of relevant scales (e.g., PFS, QoL, TCM syndrome score, other fatigue scales etc.) or physical tests indicators (e.g., cytokines, blood test etc.). The most common herbs found in Chinese medicine were Astragali Radix, Ginseng Radix and Codonopsis Radix. Some TCM products, such as Kangai Injection, Buzhong Yiqi Decoction and Shenqi Fuzheng Injection could provide a reference for medication in this review. A range of non-serious, reversible adverse effects associated with the use of TCM was also reported. However, the result of evaluation showed that none of the trials fully met all the CONSORT-CHM criteria, the quality of included trials was generally poor and the risk of bias was mostly uncertain. Conclusion There is some evidence supporting the efficacy and safety of TCM in managing CRF in this systematic review. However, no clear conclusion can be made due to the inadequate reporting of efficacy and adverse reactions. In view of some concerns about the existing evidence after the evaluation, it is essential to standardize the comprehensive identification and efficacy measurement standards, improve the quality of RCTs and conduct more multicomponent therapies to provide an updated reference for CRF patients medication in the future. The protocol of this systematic review has been registered on PROSPERO (CRD42023413625). [ https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023413625 ].